Kemampuan Metakognisi Siswa Berdasarkan Gaya Belajar Dalam Pemecahan Masalah Matematika - Andi Hasliyati Ike Safitri; Ilham Dwi Novaldin; Putri Agustina (FKIP Universitas Mataram, 2026)
Mathematical problem-solving ability is one of the essential competencies that students must possess in solving non-routine mathematical problems, as it requires higher-order thinking skills. Metacognitive ability plays an important role in students' mathematical problem-solving processes. However, each student has different metacognitive abilities, one of which is influenced by their learning style characteristics. This study employed a descriptive qualitative approach and aimed to investigate students' metacognitive abilities based on the learning styles of MTs students in solving non-routine mathematical problems. The research was conducted as a descriptive qualitative study. The research subjects were selected based on auditory, visual, and kinesthetic learning style categories. Data were collected through non-routine mathematical problem-solving tests, learning style questionnaires, and interviews to reveal students' metacognitive thinking processes. Data analysis was carried out by referring to the stages of metacognition, namely Awareness, Regulation, and Evaluation. The results showed that students' metacognitive abilities differed at each metacognitive stage across the three learning styles. Visual learners demonstrated more comprehensive metacognitive abilities, while auditory and kinesthetic learners still experienced difficulties, particularly at the evaluation stage. Nevertheless, all three subjects were able to obtain correct final solutions to the problems. These findings indicate that learning styles influence the characteristics of students' metacognitive processes in solving non-routine mathematical problems.